Trans-national Initiatives For Enhancing The Training Of Trainers And TVET Teachers In Europe And What Can Be Learnt From Them - M.A., Gerald Thiel (Journal of Technical Education and Training, 2009)
The contribution provided for the conference presents initiatives which have been launched within last year in order to improve training of trainers and TVET teachers all over Europe by establishing Europe-wide standards and networks relating national debates to European issues. For the purpose of better understanding, the background will be shortly described against which all European activities in the area of education and training nowadays should be considered; the Lisbon Agenda from 2000 and all processes related to or derived from it, as the Bologna process in the field of tertiary education, the Copenhagen process in the area of VET, and, in particular, the set-up of the European Qualification Framework for Lifelong Learning (EQF) which is now available as a Europe-wide usable reference grid to describe national and sectoral qualification systems in terms of learning outcomes, intended to enhance transparency of certificates all over Europe for various purposes , as mobility of students, employees and competition with regard to efficiency of learning, etc. It will then be highlighted which initiatives at European level have been undertaken in order to support specifically the improvement of trainers’ and TVET teachers competences with the help of the EQF. After a short overview of some studies and papers initiated by the European Commission and CEDEFOP, the European Centre of Vocational Training Development, the presentation will focus on the European Training of Trainers Network (TTNet) and the initiative to establish a European Competence Framework for VET Professions. Taking in account that the overall aim of the framework should be to support the quality of vocational teaching and training in Europe, which includes finally the delivering of benchmarks for best practice, it will be shown that it is problematic to start with (national) occupational profiling (resp. curricula) and corresponding activities of trainers and VET teachers, and to assign them to EQF levels; Profiles often have to be considered as bundles of obligations which are not necessarily directly oriented to the general objective of delivering best training, but reflect more on the specific (institutional, market) conditions under which training is carried out. These circumstances (as dealing with administrative or financial matters) are nearly always connected to specific national settings resp. traditions, not necessarily to be considered as a model for improving the system of training the trainers elsewhere. Before setting up a competence framework in the field of training trainers and TVET teachers, we regard it therefore as crucial to determine clearly the actual domain of trainers’ or TVET teachers who work independently from specific national environments, and then to relate national profiles to it. Taken as starting point the work process and training requirements derived from it (incl. the needs arising from the change of work processes) some general recommendations will be made how trans-national standards can be used successfully as an instrument to enhance training of trainers or TVET teachers and TVET in general.